Muakhi (Brotherhood) and its practices related to preventing communal conflict in multicultural societies - Hartoyo Hartoyo (Masyarakat, Kebudayaan dan Politik, 2019)
In preventing communal conflict, the role of local wisdom is often considered to be a mechanism to maintain the peacefulness and closeness of inter-ethnic relations. Many researchers also argue that conflict prevention should practiced during both pre- and post-conflict. This study, therefore, aims to explain the role of Muakhi as the local wisdom in Lampung Province for recovering inter-ethnic relations in post-communal (inter-ethnic) conflict based on two empirical cases, namely the Balinuraga conflict in South Lampung and the Pematang Tahalo conflict in East Lampung, Lampung Province. The data was collected through in-depth interviews and documents. A total of 74 informants, consisting of local residents and community leaders from Lampung, Java and Bali ethnics totaling as many as 60 people (each village 15 people). There were also 14 informants who were village, district and regency government officials, including the police department and military personnel. The data was analyzed through a qualitative approach based on the constructivist paradigm. The study found that Muakhi refers to the concept of brotherhood accepted by the immigrants who are both ethnic Balinese and Javanese. Thus, this study suggests that the practice of Muakhi in the post-communal conflict through the strengthening of the moral values and the sociocultural relationship is an effective way of restoring communal conflict. However, this study argues that there is resistance to using Angkon Muakhi in a more detailed ceremony.